Regulation of B-Cell Activation by Complement Receptors CD21 and CD35 - Erdei, Anna; Prechl, Jozsef; Isaak, Andrea; Molnar, Eszter (Current Pharmaceutical Design, 2003)
The role of complement in the development and regulation of antibody responses under both healthy and pathological conditions is known for long. Unraveling the elements involved and the molecular mechanisms underlying the events however is still in progress. This review focuses on the role of complement receptors CR1 (CD35) and CR2 (CD21) expressed on B lymphocytes, which interact with ligands generated upon activation of component C3, the major protein of the complement cascade. The binding and possible effects of immune complexes comprising antigen, antibody and complement on B-cell activation are discussed. Results of clinical studies of autoimmune diseases such as systemic lupus erythematosus and rheumatoid arthritis and conclusions drawn from animal models used to investigate various aspects of human diseases are also debated. We discuss similarities regarding the overall structure and certain functions of complement and complement receptors in mice and men however, call the attention to major differences regarding tissue distribution and their role in B-cell functions.
Keywords: b cell